2007
DOI: 10.1590/s1806-83242007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Bmp-4, Shh and Wnt-5a transcripts during early mice tooth development by in situ hybridization

Abstract: A comparative nonisotopic in situ hybridization (ISH) analysis was carried out for the detection of Bmp-4, Shh and Wnt-5a transcripts during mice odontogenesis from initiation to cap stage. Bmp-4 was expressed early in the epithelium and then in the underlying mesenchyme. Shh expression was seen in the odontogenic epithelial lining thickening, being stronger in the enamel knot area, during the cap stage. Wnt-5a transcripts were expressed only in the mesenchyme during the initiation, bud and cap stages, with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…During tooth crown formation, the cells in the inner enamel epithelium differentiate into ameloblasts that form the enamel. The inner enamel epithelium at this stage expresses both Shh and Ptch [24,[49][50][51][52][53][54], and suppression of these expressions results in the inhibition of the proliferative activity of the epithelial cells [35]. In addition, it has been demonstrated that inhibition of Shh signaling in tooth germ using a neutralizing antibody suppresses ameloblast differentiation [36].…”
Section: Shh Regulates Enamel Formationmentioning
confidence: 99%
“…During tooth crown formation, the cells in the inner enamel epithelium differentiate into ameloblasts that form the enamel. The inner enamel epithelium at this stage expresses both Shh and Ptch [24,[49][50][51][52][53][54], and suppression of these expressions results in the inhibition of the proliferative activity of the epithelial cells [35]. In addition, it has been demonstrated that inhibition of Shh signaling in tooth germ using a neutralizing antibody suppresses ameloblast differentiation [36].…”
Section: Shh Regulates Enamel Formationmentioning
confidence: 99%
“…In tooth germ mesenchyme, gene expressions of Wnt-5a and Wnt-10a have been reported 4), 5), 16) . For Wnt-10a in particular it has been reported that the expression was observed in enamel knot in early tooth germ, then shifted to the underlying mesenchymal cells, and was observed in preodontoblasts and odontoblasts at a later stage 5) .…”
Section: Wnt/ß-catenin Signaling Pathways In Odontoblasts and Progenimentioning
confidence: 99%
“…In situ hybridization (ISH) was performed as previously described (Wu and Oh 1996) with the sonic hedgehog (Shh) gene being used as a positive control (Nunes et al 2007) and the sense riboprobe being used as a negative control. Color development of the hybridization signal was performed between 2-4 h.…”
Section: T T C G a A A A At G Ata T T T C C A A A G T T T G C A G G Amentioning
confidence: 99%